ANALISIS FAKTOR-FAKTOR DALAM KUALITAS KEHIDUPAN KERJA (QUALITY WORK LIFE) DI FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Umi Widyastuti; Dedi Purwana (Jurnal Ilmiah Econosains, 2012)
Abstract Many factors determine the meaning of quality of work life (QWL). This research reviews the factors of QWL based on models and past research. The factors of QWL discussed are balance between life and non life, the work itself, skill utilization, working condition, job involvement, co-worker relationship, promotion, salary and supervisory. Confirmatory Factor Analysis is used to determine dominant factors of QWL. This research concludes that all the factors we discussed have the value of Keiser Meyers Oklin Measure of Sampling Adequacy more than 0.5, except salary. It means that eight factors which determine QWL are balance between life and non life, the work itself, skill utilization, working condition, job involvement, co-worker relationship, promotion and supervisory. After varimax rotation process and based on criteria eigenvalue more than 1, this research has formed two component from all the factors. Component 1 consist of the factor: balance between life and non life, working condition, promotion and supervisory. And component 2 consist of the factor: work itself, skill utilization, job involvement and co-worker relationship.